Magnetic integration techniques in solid state transformer - Yang, Hong Sheng (2019)
Solid State Transformer (SST) is gaining its popularity due to the disadvantages of the conventional distribution transformer such as heavy weight, bulky size, core saturation limit and harmonics in output current. SST is made up of multi-stage power electronic converters isolated with high-frequency transformer. In 2010, the proposal of SST is regarded as one of the top 10 emerging technologies by MIT Technology Review. The high frequency transformer is located in the converter, the DC-DC stage of SST. Before understanding and to design the DC-DC converter, clear understanding of the individual passive components and working principles of basic converters are required. The first half of the report covers the concepts for converter design such as working principles of buck and boost converter, rectifier, inverter and resonance tank. The lower half of the report includes evaluations on the designed converter, inductor and transformer. The evaluations describe efficiency of the converter and transformer core, as well as the characteristics of inductor and transformer.